DRY GOOSEBERRY (Physalis peruviana L) WITH PRETREATMENT OF OSMOTIC DEHYDRATION - Adriana M. CASTRO (Universidad de Antioquia, 2009)
This study find the air temperatures for dehydrating Cape gooseberry, (Physalis peruviana L), with osmotic dehydration as a pretreatment, using a solution of sucrose of 70 o Brix to 40 oC by 16 hours. The highest level of β-carotene degradation, 98%, due to the effects of oxygen, temperature and provitamin lixiviation, takes place with the pretreated fruits, which dry at 60ºC. Lixiviation contributes to 80% of this. The fruits without pretreatment and dry at a temperature of 40ºC suffer a lower level of β-carotene degradation, 28%. The times for the untreated fruit, to reach a moisture level close to 2.5%, decrease as the air temperature increase (40, 50 y 60ºC, 12, 9 and 7 hours respectively). In the case of the pretreated fruit, the drying times are 4, 5, and 6 hours for 60, 50 y 40ºC respectively. Degradation kinetic is first order. The economic study find that the cost for dehydrating at 60°C for the untreated fruit was the most suitable with an approximately cost of $374.42/Kg of fruit.